Miscellanea Miridologica II. New combinations and new synonymies in the tribe Mirini (Hemiptera: Heteroptera: Miridae) - Chérot, F.; Costa, L.; Touchet, M. (Zootaxa, 2011)
Six new synonymies and four new combinations are proposed: Guianella Carvalho 1946 = Boliviomiris Carvalho, 1987 and Pilosicerus Carvalho, 1992 (new subjective junior synonyms). Guianella pilosa Maldonado & Carvalho, 1981 = G. antennalis (Carvalho, 1987) and G. rondoniensis (Carvalho, 1992) (new subjective junior synonyms). Urucuiana Carvalho & Rosas, 1965 = Bahiamiris Carvalho, 1975 (new subjective junior synonym). Urucuiana tuberculata Carvalho & Rosas, 1965 = U. cajabiana (Carvalho, 1977) (new subjective junior synonym). Guianella antennalis, G. rondoniensis, U. cajabiana, and U. rubrornata (Carvalho, 1975) (new combinations). Urucuiana tuberculata is reported from French Guyana for the first time.